Craniofacial morphology and its association with masseter and medial pterygoid muscle thickness among adults from a population-based sample - Annalena Spilz; Christian Schwahn; Karl-Friedrich Krey; Robin Bülow; Henry Völzke; Markus Krüger; Amro Daboul (Clinical Oral Investigations, 2026)
Abstract Objectives The association between craniofacial morphology and the cross-sectional areas (CSA) of the masseter and medial pterygoid muscles using Procrustes-based geometric morphometrics on magnetic resonance imaging (MRI) data was investigated. Materials and methods This cross-sectional study included 692 participants from the first examination wave of the second cohort of the population-based Study of Health in Pomerania (SHIP-TREND-0). Craniofacial landmarks were identified on MRI scans, and muscle CSAs were measured using image segmentation techniques. Principal component (PC) analysis was used to assess morphological variation. Regression models adjusted for sex, age, education, dental status, body height and weight, and centroid size were used to estimate associations between craniofacial shape and muscle CSA. Results PC1, which primarily captured facial height and cranial base length, and PC2, which represented maxillary width and facial prominence, were associated with medial pterygoid muscle CSA. Longer faces (PC1) were associated with thinner pterygoid muscles, while wider midfaces (PC2) were associated with larger CSA ( P = 0.0038 and P = 0.0005, respectively). Partial R² of PC1 through PC7 was 0.038 for pterygoid muscles and 0.016 for masseter muscles ( P < 0.0001 and P = 0.0225 for joint tests, respectively). There was a stronger association between number of teeth and masseter muscles than with pterygoid muscles (partial R² 0.076 and 0.026, respectively). Conclusions Craniofacial variation, particularly in terms of facial height and midface width, was associated with the medial pterygoid muscle rather than the masseter muscle. Clinical relevance Associations suggest a potential anatomical basis for the study of myofunctional disorders.